Development of antimicrobial soaps using essential oil of Schinus terebinthifolius and Piper nigrun (Research, Society and Development, 2020)
A cosmetic product consists of natural or synthetic substances, the purpose of which is to wash, scent, correct and protect the various parts of the human body. Human skin has pores that connect to the oil glands, which produce sebum, an oily liquid that carries dead cells through the hair follicles to the surface of the epidermis, causing the appearance of skin lesions and the growth of microorganisms. In the present work, two antimicrobial soaps were formulated in solid and liquid form using essential oil of Schinus terebinthifolius and Piper nigrun, analysed and compared with other antimicrobial soaps available on the market. In addition, the microbiological safety of the products developed was tested, according to ANVISA criteria. All products developed in this work have microbiological safety, but the best inhibitory results regarding the growth of the microorganisms Staphylococcus aureus and Escherichia coli were obtained with the soaps in liquid form.